Efektivitas Pelaksanaan Program Dana Bantuan Operasional Sekolah Reguler (BOS Reguler) di SMAN Bali Mandara Singaraja - I.P. Sudiarna; A.A.G. Agung; I.N. Natajaya (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aimed to determine the effectiveness of the Regular School Operational Assistance (BOS) program at SMAN Bali Mandara in terms of context, input, process, and product variables. This research was an empirical study (expost facto), the evaluation was conducted by using the CIPP model, in which the research population were the community of SMAN Bali Mandara with a sample of 35 people determined by purposive sampling technique. Data were collected by using questionnaires, interviews, documentation, and observation. Data analysis used standard score or Z-score which was then transformed into T-score. To determine the level of effectiveness of BOS fund users, an analysis of context, input, process and product variables was carried out through analysis of the Glickman prototype quadrant. The results showed that the effectiveness of the Regular BOS fund program at SMAN Bali Mandara belonged to very effective category seen from context variables of 20.00%, input variables of 42.86%, process variables of 31.43%, and product variables of 37.14%. Overall, the results of the calculation from context, input, process, and product variables simultaneously produced (+ + + +). Although it was very effective, there were several obstacles faced, namely the input and process variables. It was recommended to (1) the Principal of SMAN Bali Mandara to continue the collaboration and coordination with the government so that for next year the management of Regular BOS funds could conduct the program well, smoothly and effectively; (2) The Provincial Government of Bali, especially Disdikpora (Department of Education, Youth and Sport) Bali Province, should pay more attention to providing guidance in every quarter or at least every semester to schools, especially in reporting and bookkeeping; (3) The Directorate General of PAUD Dikdasmen Kemdikbudristek (Basic and Middle Education, the Ministry of Education, Culture, Research and Technology) should pay attention to the schedule of Regular BOS distribution so that it was clear and there were no technical changes in the middle program.